2021
DOI: 10.1080/25785826.2021.1919342
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestations in anti-Ro52/SS-A antibody-seropositive patients with Sjögren's syndrome

Abstract: Background: The relationship between anti-Ro52/SS-A antibody (anti-Ro52) and the clinical manifestations of Sj€ ogren's syndrome (SS) has not been fully clarified. We determined the clinical factors relevant to SS patients with anti-Ro52. Methods: We conducted a retrospective study of 149 subjects suspicious for SS and 50 healthy control subjects. We analyzed items of the American-European Consensus Group (AECG) criteria and the EULAR Sj€ ogren's Syndrome Disease Activity Index (ESSDAI). Results: SS was docume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…This may be related to the limited number of patients with C-pSS and the relatively low probability of organ involvement in our study. Third, a close association between immunological markers and other laboratory indications identified in our study has also been reported in previous studies (32,34,38). We confirmed that IgG levels increased significantly in patients with positive anti-SSA/Ro52 or anti-SSA/Ro60.…”
Section: Discussionsupporting
confidence: 92%
“…This may be related to the limited number of patients with C-pSS and the relatively low probability of organ involvement in our study. Third, a close association between immunological markers and other laboratory indications identified in our study has also been reported in previous studies (32,34,38). We confirmed that IgG levels increased significantly in patients with positive anti-SSA/Ro52 or anti-SSA/Ro60.…”
Section: Discussionsupporting
confidence: 92%
“…Our markedly higher ESSDAI in our cohort may be explained by the manifestations of cryoglobulinaemia including cutaneous vasculitis and Raynaud’s phenomena ( Table 2 ). The incidence of cryoglobulinaemia was not explored in these earlier studies ( 4 , 14 ); however, the isolated anti-Ro52 subset positively correlated with RhF ( 4 , 12 , 14 ), consistent with our findings ( Table 2 ). Moreover, a cross-sectional study in a laboratory cohort of SS patients that measured cryoglobulins in serological subsets, found that isolated anti-Ro52 antibodies were associated with cryoglobulinaemia ( 32 ).…”
Section: Discussionsupporting
confidence: 90%
“…In SS, anti-Ro52 positivity may signify a severe subset of patients associated with rheumatoid factor (RhF) positivity ( 12 , 13 ). However, the value of stratifying SS patients by patterns of serum autoantibodies (anti-Ro52, anti-Ro60 and anti-La) has not been widely appreciated and inconsistencies remain in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the immunosuppressive function of SoJIA-driven PBCECs, we investigated the monocyte responsiveness to lipopolysaccharide (LPS) in the presence or absence of PBCECs obtained from patients with SoJIA. We focused on the effect of CECs on monocytes but not lymphocytes, as SoJIA is an autoinflammatory disease involving excessive hypercytokinemia triggered by the activation of the innate immune system 35 , 36 . PBCECs were procured in combination with magnetic microbeads and fluorescent cell sorting from patient’s PBMCs to obtain a > 96% purity population (Fig.…”
Section: Resultsmentioning
confidence: 99%